Dick pics and the shifty meanings of porn - Paasonen, Susanna (United Kingdom, 2025)
Dick pics are ubiquitous objects in social media shared for the purposes of harassment, flirtation, suggestion, amusement, and titillation alike. Starting with the question of how dick pics are, or are not classifiable as porn, this article opens up lines of inquiry on the possibilities and limitations of porn as a genre marker, content classifier, and reference point in and for understanding sexual content distributed through networked means. In the contemporary moment when sexual content continues to multiply online even as most social media platforms vigilantly moderate and remove it, scholarly vocabularies risk either lagging behind or posing normative categorisation on the things published and shared, from dick pics to webcam shows and OnlyFans content. This article calls for contextual care in how the notion of porn becomes applied to networked sexual media, the shapes of continue to morph, as well as in how dick pics are made sense of as communication devices and cultural symbols.